2022
DOI: 10.3390/ijerph19148562
|View full text |Cite
|
Sign up to set email alerts
|

Italian Validation of the 12-Item Version of the Burnout Assessment Tool (BAT-12)

Abstract: The Burnout Assessment Tool (BAT) has shown satisfactory validity evidence in several countries, with the 23-item version of the instrument reporting adequate psychometric properties also in the Italian context. This paper is aimed to present results from the Italian validation of the 12-item version of the BAT. Based on a sample of 2277 workers, our results supported the factorial validity of a higher-order model represented by 4 first-order factors corresponding to the core dimensions of burnout, namely exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 65 publications
2
17
0
4
Order By: Relevance
“…In line with the presented conceptual underpinning, previous studies validating BAT-12 showed that the second-order model is supported on samples from Belgium and the Netherlands (Schaufeli et al, 2020a), Brazil and Portugal (Sinval et al, 2022), Ecuador (Vinueza-Solórzano et al, 2021, Italy (Mazzetti et al, 2022), Romania (Oprea et al, 2021), andSouth Africa (de Beer et al, 2022a). This study contributes to these research efforts by testing the proposed model for the first time in Croatia.…”
Section: Validation Of the Croatian Version Of Bat-12supporting
confidence: 71%
See 3 more Smart Citations
“…In line with the presented conceptual underpinning, previous studies validating BAT-12 showed that the second-order model is supported on samples from Belgium and the Netherlands (Schaufeli et al, 2020a), Brazil and Portugal (Sinval et al, 2022), Ecuador (Vinueza-Solórzano et al, 2021, Italy (Mazzetti et al, 2022), Romania (Oprea et al, 2021), andSouth Africa (de Beer et al, 2022a). This study contributes to these research efforts by testing the proposed model for the first time in Croatia.…”
Section: Validation Of the Croatian Version Of Bat-12supporting
confidence: 71%
“…The reported findings corresponding to the H 1 and H 2 complement previous studies testing the latent structure of the BAT-12, which are still relatively scarce. With the exception of previously described studies testing the alternative latent structures of BAT-12 (Mazzetti et al, 2022;Oprea et al, 2021;Schaufeli et al, 2020a) detailed information on the nature of relationships (Greiff & Scherer, 2018). For future research that decides using different age groups, our results can be informative for establishing age cut-off points.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…No gender differences emerged with regard to mental distance. According to some scholars [ 84 , 92 ], mental distance is a feeling of psychological detachment characterized by a scarcity of motivation, interest, and enthusiasm [ 84 , 92 ]. High levels of mental distance reveal a strong aversion toward the job and are related to feelings of cynicism toward one’s work [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%